The Effect of a 12-Week Health Training Program on Selected Anthropometric and Biochemical Variables in Middle-Aged Women - Pilch, Wanda (Biomed Res Int, 2017)
Regular moderate physical activity positively affects health, fitness, and body composition; it regulates the pro- and anti-inflammatory cytokines levels. Vitamin D plays an important regulatory role; its adequate levels correlate with low values of inflammation markers and an increase in muscle strength and fitness in exercising people. The study's aim was to evaluate changes in somatic variables, oxidative stress, and inflammation markers, as well as blood calcidiol concentration in middle-aged healthy women after 12 weeks of aerobics classes—endurance exercises, including choreographic sequences, aiming to improve fitness and motor coordination. The training led to a significant reduction of body mass and fat tissue; it induced an increase in lean body mass. After the 12-week training program, plasma antioxidant status increased (0.65 ± 0.21, p < 0.01) and the concentration of lipid peroxidation products decreased (0.07 ± 0.02, p < 0.001). A significant increase in plasma antioxidant status associated with training could have reduced the level of proinflammatory interleukin as indicated by a positive correlation between these variables (r(s) = 0.64, p < 0.05). The study proved that a 12-week health training program in physically inactive middle-aged women might provide improvements in their anthropometric parameters and selected biochemical indicators.